2003
DOI: 10.1046/j.1460-9592.2003.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral high‐dose midazolam premedication for infants and children undergoing cardiovascular surgery

Abstract: Oral midazolam 1.5 mg x kg(-1) is excellent for preanaesthetic medication for infants and children undergoing cardiovascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…According to the available safety data from the studies, higher midazolam doses generally resulted in a higher incidence of adverse events and of cases of over‐sedation (particularly 1‐1.5 mg/kg doses). It has been shown that doses of midazolam higher than 0.5 mg/kg may be associated with increased levels of adverse events such as loss of balance and head control, dysphoria and blurred vision, hypotension, respiratory depression, dysphoric reactions, and ataxia and lead to a higher incidence of deep sedation . Cases of deep sedation with an oral dose of 0.5 mg/kg have also been reported …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the available safety data from the studies, higher midazolam doses generally resulted in a higher incidence of adverse events and of cases of over‐sedation (particularly 1‐1.5 mg/kg doses). It has been shown that doses of midazolam higher than 0.5 mg/kg may be associated with increased levels of adverse events such as loss of balance and head control, dysphoria and blurred vision, hypotension, respiratory depression, dysphoric reactions, and ataxia and lead to a higher incidence of deep sedation . Cases of deep sedation with an oral dose of 0.5 mg/kg have also been reported …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that doses of midazolam higher than 0.5 mg/kg may be associated with increased levels of adverse events such as loss of balance and head control, dysphoria and blurred vision, hypotension, respiratory depression, dysphoric reactions, and ataxia 9,16,18 and lead to a higher incidence of deep sedation. 18,21,23 Cases of deep sedation with an oral dose of 0.5 mg/kg have also been reported. 24 It was noted that some of the adverse events reported are observed when oral midazolam is used in combination with other drugs (following induction of anesthesia, or after administration of treatments used for local anesthesia, or other medications required for the respective interventions) and can therefore not be attributed to midazolam treatment exclusively.…”
Section: Safetymentioning
confidence: 99%
“…Results are comparable with the present study. There are other studies which used 1 mg/kg [17] and 1.5 mg/kg [29] of oral midazolam and found that the children were better sedated than with the standard dose (0.5 mg/kg) of midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…With a success rate of 96%, our results favorably compare with the results reported with other techniques. Indeed, since the introduction of modern imaging (CT and MRI), radiologists and pediatricians have attempted to determine the most effective and safest sedation strategy [14][15][16][17], barbiturates (pentobarbital [5,11,18], methohexital [19][20][21] or thiopental [22][23][24]) and a number of other compounds like chloral hydrate [6,18,25], etomidate [26] and propofol [4,27,28] have been tested (Table 6). With these protocols, sedation has been reported to be effective in 80-100% of patients.…”
Section: Discussionmentioning
confidence: 99%